Differentially expressed genes in plants : a bench manual - Hansen, E. (Ekkehard); Harper, G. (Glyn) (Taylor & Francis, 1997)
The analysis of changes in gene activity in tissues and cells of plants is a way of measuring developmental and environmental responses. This volume provides detailed accounts of new and established techniques used to carry out such analyses.